Oxford Scholarship Online 2018
DOI: 10.1093/oso/9780190456023.003.0018
|View full text |Cite
|
Sign up to set email alerts
|

Relationality, Reciprocity, and Flourishing in an African Landscape

Abstract: The chapter considers the environmental ethics underlying certain practices and beliefs observed in the course of field research with primarily ||Khao-a Dama people in west Namibia. ||Khao-a Dama perspectives embody a type of “relational environmental ethics” that refracts anthropocentric/ecocentric dichotomies, and is characterized by respect for, and reciprocity with, agency and intentionality as located in entities beyond the human (ancestors, spirits, animals, healing plants and rain). The chapter connects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Eco psychology, together with ecophilosophy and phenomenology approaches to human experience, specifies that psychological disintegration arising in connection with the commodity form is also ecological in nature (see Evernden, 1985; Roszak, 2002). Psychological integration thereby implies recognition of the virtues of ecological dependence (Hannis, 2016) to extend human relational and reciprocal practices to include natures-beyond-the-human (Hannis and Sullivan, 2018).…”
Section: Accumulation-by-alienation and The Structural Natures Of Ecomentioning
confidence: 99%
“…Eco psychology, together with ecophilosophy and phenomenology approaches to human experience, specifies that psychological disintegration arising in connection with the commodity form is also ecological in nature (see Evernden, 1985; Roszak, 2002). Psychological integration thereby implies recognition of the virtues of ecological dependence (Hannis, 2016) to extend human relational and reciprocal practices to include natures-beyond-the-human (Hannis and Sullivan, 2018).…”
Section: Accumulation-by-alienation and The Structural Natures Of Ecomentioning
confidence: 99%
“…While the conflict-laden relationships between ontologies have been productively analyzed (Blaser 2013a;Hannis and Sullivan 2018), it is seldom thematized that worlds increasingly overlap. In Namibia some Damara people are scientists, some are teachers, and many know in multiple ways.…”
Section: Inter-ontological Relationshipsmentioning
confidence: 99%
“…Environmental studies is another field in which the many-worlds model has been productively mobilized (De la Cadena and Blaser 2018;Descola 2013;Green 2013;Omura et al 2018;Whatmore 2002). During the last decade, several authors have convincingly demonstrated that thingsincluding rivers and lakes (Mészáros 2020), fires (Verran 2002), landscapes (Hannis and Sullivan 2018;Sullivan 2017), forests (Kohn 2013), and many more entities-can become so different that it makes sense to speak of entirely different entities. This is the case with the winds I study: depending on how one relates to them, they can be either a person or a resource for powering a windmill that pumps water for people and their livestock (Schnegg 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, in northwestern Namibia the rain is an all-encompassing phenomenon, and others have offered sophisticated analyses of its additional meanings. These include how the lack of rain is a consequence of social and political change (Sullivan, 2002), rain's personified agency (Hannis and Sullivan, 2018; Schnegg, 2019) and rain's symbolic, medical and ritual role in rock art and people's lives (Low, 2008; Sullivan and Low, 2014). Moreover, I have shown in my previous work how two gendered and animated winds are responsible for the arrival of the rains and how and why the rains have failed to come in recent years with climate change (Schnegg, 2019, 2021).…”
Section: How Different Rains Encapsulate Timementioning
confidence: 99%